MOLTING OF BROILER BREEDERS CONDITIONS FOR ECONOMIC JUSTIFICATION IN CONTINUED PRODUCTION - Pesić, Bratislav; Stolić, Nikola; Milošević, Božidar; Spasić, Zvonko (Economics of Agriculture, 2016)
The method of artifcial interruption of the production process by hens, broiler breeders, today known as the molting, it is often used in recent years as one of possible reasonable steps in making decisions on feasibility of continuing exploitation of broiler breeder safter the regular production process. The aim of this study was to test the economic proftability molting hens-broiler, during one exploitation period. It included the throat of hybrid heavy line COBB500. The animals in the house were exposed to the same microclimate conditions, with identical positions in relation to light, ventilation, water, food and fertilization system. The analysis of food consumption per produced egg can be notice that parents hens during the process of molting consume more food by 43% compared to the hens fed the normal cycle of production. Achieved income was 2.54% higher after billing code for molting chickens instead of the regular production cycle. Economic indicators egg production after molting demonstrate justifcation of these biological and technological operations, considering that the net income per hen housed is the same income in the normal production process.